Revived: The Journey Within - Khadija Malik Hassan (Karachi,Pakistan Still Waters Pub., 2008)
The Revived jewellery collection and philosophy is the brainchild of Kiran Aman. The Revived collection comprises of four series, each of which has been designed to express the different aspects of Woman. The collection allows a woman to find the depiction of her inner state by choosing the motif that is most appealing to her. Revived the philosophy is related to the lives of 14 women. Amongst them are some of the powerhouses of Pakistan$1 (Bs fashion industry, and others have contributed towards its growth while working in their own domains of journalism and design. s
Includes Colored Illustrations and Index